Origins Matter: Culture Impacts Cognitive Testing in Parkinson’s Disease - Statucka, Marta; Cohn, Melanie (Frontiers in Human Neuroscience, 2019)
Cognitive decline is common in Parkinson’s disease (PD), and precise cognitive assessment is important for diagnosis, prognosis, and treatment. To date, there are no studies in PD investigating cultural bias on neuropsychological tests. Clinical practice in multicultural societies such as, Toronto Canada where nearly half of the population is comprised of first generation immigrants, presents important challenges as most neuropsychological tools were developed in Anglosphere cultures (e.g., USA, UK) and normed in more homogeneous groups. We examine total scores and rates of deficits on tests of visuoperceptual/visuospatial, attention, memory, and executive functions in Canadians with PD born in Anglosphere countries (n = 248) vs. in Canadians with PD born in other regions (International group; n = 167). The International group shows lower scores and greater rates of deficits on all visuoperceptual and some executive function tasks, but not on attention or memory measures. These biases are not explained by demographic and clinical variables as groups were comparable. Age at immigration, years in Canada, and English proficiency also do not account for the observed biases. In contrast, group differences are strongly mediated by the Historical Index of Human Development of the participants’ country of birth, which reflects economic, health, and educational potential of a country at the time of birth. In sum, our findings demonstrate lasting biases on neuropsychological tests despite significant exposure to, and participation in, Canadian culture. These biases are most striking on visuoperceptual measures and non-verbal executive tasks which many clinicians still considered to be “culture-fair” despite the growing evidence from the field of cross-cultural neuropsychology to the contrary. Our findings also illustrate that socio-development context captures important aspects of culture that relate to cognition, and have important implications for clinical practice.